Sitagliptin improves plasma apolipoprotein profile in type 2 diabetes: A randomized clinical trial of sitagliptin effect on lipid and glucose metabolism (SLIM) study. (April 2020) - Tanimura-Inagaki, Kyoko; Nagao, Mototsugu; Harada, Taro; Sugihara, Hitoshi; Moritani, Shigeki; Sasaki, Jun; Kono, Suminori; Oikawa, Shinichi; ,
Abstract: Aim: This study aims to evaluate the effect of dipeptidyl peptidase-4 inhibitors on lipid metabolism in patients with type 2 diabetes mellitus (T2D). Methods: This is a multicenter, open-labeled, randomized controlled study. T2D patients with HbA1c 6.9–8.9% (52–74 mmol/mol) who were under treatment with sulfonylurea were randomly allocated to either the sitagliptin group or the non-sitagliptin group. Glucose and lipid metabolism parameters including apolipoproteins (apo), sterols, and urinary albumin were assessed at baseline, 3, and 6 months of the treatment. Results: A total of 164 patients completed the 6-month observation (n = 81 for sitagliptin and n = 83 for non-sitagliptin). HbA1c decreased in the sitagliptin group but not in the non-sitagliptin group. Serum TG and total, LDL and HDL cholesterol levels did not change in either group. Apo B-48, apo CII, and apo CIII levels decreased in the sitagliptin group, but not in the non-sitagliptin group. The change in urinary albumin was significantly different between the groups with a preferable change in the sitagliptin group. There were no changes in serum sterols levels in the two groups. Conclusions: The treatment of sitagliptin for 6 months improves the metabolism of glucose and chylomicron and reduces plasma levels of atherogenic lipoproteins in patients with T2D.